Students' perceptions of academic planning effectiveness in Nigerian universities (2014)
The problem of inadequate and insufficient infrastructural facilities is not new as several scholars have investigated it over the years. However, the role of the academic planning unit in Nigerian universities has not been investigated as the section is often down played when selecting items and areas to investigate. With the attention generated on the insufficiency of infrastructure, several interventionist policies that have been adopted by government who is almost sole investor in public universities. This study therefore investigated the effectiveness of such planning from the perspective of students who utilize such infrastructure. The study adopted the survey research design using the multi stage sampling procedure to select 3,340 student respondents from five faculties in Nigeria's first and second generation universities. A simple instrument titled 'Students Perception of Academic Planning Questionnaire' r-0.87 was used to elicit responses from respondents. The instrument was divided into two sections with section A eliciting bio-data information and section B on academic planning effectiveness (infrastructure). 2 research questions guided the study and were answered using simple descriptive statistics as percentages and frequency counts. The study found that of all the items surveyed; adequacy of library, health centre, hostel facilities, classrooms, Information Communication Technology (ICT) equipment, laboratory facilities, only ICT and laboratories scored a medium score. All others scored low as shown in Table 1 and 2. The impact of recent investments is yet to be seen in the universities. It is recommended that the universities seek to be independent in fund generation to facilitate planning and timeliness.